Peculiarities of the motives to approach success and to avoid failure - Punis, A. (Psichologija, 1996)
The motive for approaching success (SS) is characterised as the capacity to anticipate pleasure or pride and the motive for avoiding failure (NV), as the capacity to anticipate pain or embarrassment. A measuring instrument for these motives has been developed by T. Gjesme and R. Nygard (the Achievement Motivation Scale, AMS). The present investigation was undertaken in order to analyse the relationship between the scores on the SS and NV scales and other possible near features. A positive and statistically reliable relationship between the SS scale and CPI Dominance scale was found, and a negative relationship between the NV and H. Eysenck Extroversion-Introversion Neurotism scale, R. Amthauer's third test and fifth subtest. It was also found that there is no direct relationship between SS and NV motives and the different attractivenesses in the process of the job, the result of the job, or the evaluation of the job.
Keywords: motivation; motive for approaching success; motive for avoiding failure